Multifrequency variability of the blazar AO 0235+164 the WEBT campaign in 2004-2005 and long-term SED analysis - Romero, Gustavo Esteban (2006)
Aims. A huge multiwavelength campaign targeting the blazar AO 0235+164 was organized by the Whole Earth Blazar Telescope (WEBT) in 2003-2005 to study the variability properties of the source. Methods. Monitoring observations were carried out at cm and mm wavelengths, and in the near-IR and optical bands, while three pointings by the XMM-Newton satellite provided information on the X-ray and UV emission. Results. We present the data acquired during the second observing season, 2004-2005, by 27 radio-to-optical telescopes. The ∼2600 data points collected allow us to trace the low-energy behaviour of the source in detail, revealing an increased near-IR and optical activity with respect to the previous season. Increased variability is also found at the higher radio frequencies, down to ∼15 GHz, but not at the lower ones. While the X-ray (and optical) light curves obtained during the XMM-Newton pointings reveal no significant short-term variability, the simultaneous intraday radio observations with the 100 m telescope at Effelsberg show flux-density changes at 10.5 GHz, which are more likely due to a combination of intrinsic and extrinsic processes. Conclusions. The radio (and optical) outburst predicted to peak around February-March 2004 on the basis of the previously observed 5-6 yr quasi-periodicity did not occur. The analysis of the optical light curves reveals now a longer characteristic time scale of variability of ∼8 yr, which is also present in the radio data. The spectral energy distributions corresponding to the XMM-Newton observations performed during the WEBT campaign are compared with those pertaining to previous pointings of X-ray satellites. Bright, soft X-ray spectra can be described in terms of an extra component, which appears also when the source is faint through a hard UV spectrum and a curvature of the X-ray spectrum. Finally, there might be a correlation between the X-ray and optical bright states with a long time delay of about 5 yr, which would require a geometrical interpretation.